Understanding What Shapes a Polycentric Governance System. (9th March 2016) - Berardo, Ramiro; Lubell, Mark
Abstract: Recent research has shown that communication networks involving governmental and nongovernmental actors self‐organize based on how risk is perceived. According to the "risk hypothesis, " actors embedded in governance systems in which there is widespread risk of defection tend to form bonding structures, whereas those in low‐risk systems form bridging structures. A parallel strand of research proposes to study complex governance systems composed of multiple actors and the decision‐making forums in which they interact. In this article, the authors couple these research threads and show how bonding and bridging structures form when stakeholders participate in three complex governance systems of varying institutional strength. Findings suggest that the prevalence of one type of structure over the other depends on contextual variables such as the stability of the institutions and the occurrence of environmental focusing events that demand quick policy responses . Abstract : Related Content:Isenberg (PAR September/October 2016)